Interferon Beta – Medication Which Started the Revolution in the Treatment of Multiple Sclerosis - Ivanovic, Jovana; Pekmezović, Tatjana; Drulović, Jelena (Medicinski podmladak, 2019)
Multiple sclerosis is a chronic, inflammatory, demyelinating and neurodegenerative disease of the central nervous system. The etiology is unknown, and it is estimated that about 2.5 million people all around the world are suffering from this disease. It is the most common cause of non-traumatic disability in young adults. The clinical presentation is very variable and unpredictable. There are three basic forms of the disease – relapsing remitting, primary progressive and secondary progressive multiple sclerosis. The prognosis for these patients has changed since 1993, when the first disease modifying therapy – interferon beta, was approved. Interferon beta reduces the number of relapses, reduces the number of hyper intense lesions on T2 sequences of endocranial MRI, mildly delaying the progression of the disease. Interferon beta is also used in pediatric population. It is considered to be generally safe, since it does not increase the likelihood of developing malignancy and opportunistic infections.